2018
DOI: 10.20535/2307-5651.15.2018.136541
|View full text |Cite
|
Sign up to set email alerts
|

Економічний Аналіз Фармацевтичного Підприємства Щодо Перспективи Інноваційного Розвитку На Прикладі Пат «фармак»

Abstract: The article considers the problem of development and competitiveness of the pharmaceutical industry companies of Ukraine as one of the leading knowledge-intensive and profitable industries in the world. The importance of development of the pharmaceutical market as one of the elements of ensuring the national security of the state is emphasized. The problem of innovation and technological development of Ukrainian economy sectors is defined as central in modern economic conditions. It is noted that it is necessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Проте, згідно опитувань, проведених фахівцями Європейської Бізнес-Асоціації [18], в 2023 р. український бізнес розпочав активізацію до свого відновлення. Так, частка підприємств, які почали працювати в повному обсязі склала 52,0 %, а тих, які працюють маючи певні обмеження -41,0 %, тих, що зовсім перестали працювати є тільки 7,0%.…”
Section: рис 2 динаміка результатів чистого прибутку (збитку) підприє...unclassified
“…Проте, згідно опитувань, проведених фахівцями Європейської Бізнес-Асоціації [18], в 2023 р. український бізнес розпочав активізацію до свого відновлення. Так, частка підприємств, які почали працювати в повному обсязі склала 52,0 %, а тих, які працюють маючи певні обмеження -41,0 %, тих, що зовсім перестали працювати є тільки 7,0%.…”
Section: рис 2 динаміка результатів чистого прибутку (збитку) підприє...unclassified
“…The systematization of scientific studies showed that many publications addressed the tools of digital marketing, their types, features of the application in various fields of economic activity, etc., including the importance of the site for enterprise development (Bozhkova et al, 2018;Davidaviciene et al, 2019;Illiashenko and Ivanova, 2015;Melnik et al, 2016;Mozgova, 2017;Oklander et al, 2020;Oklander and Oklander, 2017;Prudnikov and Nazarenko, 2021;Rosokhata, 2020;Teletov et al, 2020). The pharmaceutical companies' activities, the peculiarities of their actions, limitations, and opportunities that exist in the market were investigated by Mykhailiuk (2017); Chernousova and Mishchenko (2018); Shabelnyk (2016); Vitiuk and Trachenko (2018); Khazzaka (2019). However, there are next to no publications on analyzing the effectiveness of web management by pharmaceutical companies in the veterinary field.…”
mentioning
confidence: 99%